A Foodborne Outbreak of Staphylococcus aureus Associated with Fried Chicken in Republic of Korea - Hyeon, J.Y., Korea Centers for Disease Control and Prevention, Cheongwon, Republic of Korea; Chung, G.T., Korea Centers for Disease Control and Prevention, Cheongwon, Republic of Korea; Bing, S.H., Research Institute of Public Health and Environment, Daejon, Republic of Korea; Kwon, K.S., Research Institute of Public Health and Environment, Daejon, Republic of Korea; Lee, H.H., Seo-gu Daejon Health Center, Daejon, Republic of Korea; Kim, S.J., Korea Centers for Disease Control and Prevention, Cheongwon, Republic of Korea; Jeon, S.E., Korea Centers for Disease Control and Prevention, Cheongwon, Republic of Korea; Kang, Y.H., Korea Centers for Disease Control and Prevention, Cheongwon, Republic of Korea; Kim, J.Y., Korea Centers for Disease Control and Prevention, Cheongwon, Republic of Korea (Journal of microbiology and biotechnology, 2013)
An outbreak of Staphylococcus aureus infections occurred in a university with an enrollment of 80 students in the city of Daejon, Republic of Korea. All nine S. aureus isolates from patients (n = 7), staff members (n = 1), and the fried chicken served as the lunch (n = 1) harbored the enterotoxin A gene and showed an identical antibioticresistant profile, PFGE banding pattern (STAS16.001), and sequence type, ST 6. These results suggested that the outbreak was associated with eating the fried chicken that had been handled by an infected staff member. This case report demonstrated a practical approach to identifying the source and transmission of an infection.